Physical fitness, cognition, and structural network efficiency of brain connections across the lifespan. (15th April 2023) - Callow, Daniel D.; Smith, J. Carson
Abstract: Inadequate levels of exercise is one of the most potent modifiable risk factors for preventing cognitive decline and dementia as we age. Meanwhile, network science-based measures of structural brain network global and local efficiency show promise as robust biomarkers of aging, cognitive decline, and pathological disease progression. Despite this, little to no work has established how maintaining physical activity (PA) and physical fitness might relate to cognition and network efficiency measures across the lifespan. Therefore the purpose of this study was to determine the relationship between (1) PA and fitness and cognition, (2) fitness and network efficiency, and (3) how network efficiency measures relate to cognition. To accomplish this, we analyzed a large cross-sectional data set (n = 720; 36–100 years) from the aging human connectome project, which included the Trail Making Task (TMT) A and B, a measure of fitness (2-min walk test), physical activity (International Physical Activity Questionnaire), and high-resolution diffusion imaging data. Our analysis consisted of employing multiple linear regression while controlling for age, sex, and education. Age was associated with lower global and local brain network efficiency and poorer Trail A & B performance. Meanwhile, fitness, but not physical activity, was related to better Trail A and B performance and fitness, and was positively associated with local and global brain efficiency. Finally, local efficiency was related to better TMT B performance and partially mediated the relationship between fitness and TMT B performance. These results indicate aging may be associated with a shift towards less efficient local and global neural networks and that maintaining physical fitness might protect against age-related cognitive performance deterioration by bolstering structural network efficiency. Highlights: Age was negatively related to network efficiency measures and Trail Making Task performance. Physical fitness but not physical activity was associated with better Trail Making Task performance. Physical fitness was positively associated with global and local efficiency measures. Local efficiency measures partially mediated the relationship between physical fitness and Trail Making Task B performance.